Prawo do strajku – kompletne czy ułomne prawo człowieka? - Świątkowski, Andrzej Marian (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2025)
The author’s aim is to present Adam Podgórecki’s sociological view of human rights, including his distinction between complete and crippled rights, and to present and assess, from this perspective, the right to strike in Europe. The strikes organised by people aware of the existence of human rights, their potential and importance are almost always directed against the government in power. A number of member states of the Council of Europe are considered by the European Committee of Social Rights, which acts as the body overseeing the ‘completeness and not the imperfection’ of these rights, as institutions damaging the image of democracy in Europe. The author, based on his experience as a former member and vice-chairman of the European Committee of Social Rights of the Council of Europe, writes about the rights of employees to take collective action - legal strikes, their restrictions by the authorities of European states, and the obligations to refer collective disputes to the decisions of state bodies. In the final remarks, the author references research findings on Poles’ attitudes towards the right to strike and points to the specificity of its exercise in Poland.